2020
DOI: 10.7554/elife.51453
|View full text |Cite|
|
Sign up to set email alerts
|

Polyunsaturated fatty acid analogues differentially affect cardiac NaV, CaV, and KV channels through unique mechanisms

Abstract: The cardiac ventricular action potential depends on several voltage-gated ion channels, including NaV, CaV, and KV channels. Mutations in these channels can cause Long QT Syndrome (LQTS) which increases the risk for ventricular fibrillation and sudden cardiac death. Polyunsaturated fatty acids (PUFAs) have emerged as potential therapeutics for LQTS because they are modulators of voltage-gated ion channels. Here we demonstrate that PUFA analogues vary in their selectivity for human voltage-gated ion channels in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 64 publications
0
19
0
Order By: Relevance
“…Polyunsaturated fatty acids (PUFAs) affect many different ion channels, such as voltage-gated K + , Na + , and Ca 2+ channels, as well as ryanodine receptors ( Xiao et al, 2001 ; Hamilton et al, 2003 ; Oliver et al, 2004 ; Xiao et al, 2005 ; Ottosson et al, 2014 ; Farag et al, 2016 ; Tian et al, 2016 ; Liin et al, 2018 ; Bohannon et al, 2020 ). However, the molecular mechanisms behind the effects of PUFAs are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Polyunsaturated fatty acids (PUFAs) affect many different ion channels, such as voltage-gated K + , Na + , and Ca 2+ channels, as well as ryanodine receptors ( Xiao et al, 2001 ; Hamilton et al, 2003 ; Oliver et al, 2004 ; Xiao et al, 2005 ; Ottosson et al, 2014 ; Farag et al, 2016 ; Tian et al, 2016 ; Liin et al, 2018 ; Bohannon et al, 2020 ). However, the molecular mechanisms behind the effects of PUFAs are not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, various in vivo and in vitro studies showed that ω-3 PUFA could influence the electrophysiology of atrial and ventricular cardiomyocytes by alleviating their excitability, and cytosolic fluctuations of calcium, especially in damaged or ischemic cells that are prone to depolarization and arrhythmia [10]. Recently, in one study, the heart's electrical activity or Long QT Syndrome was described as mediated by the involvement of PUFAs [16]. PUFA analogues modulated the capacity of different voltage-gated ion channels (NaV, CaV, and KV).…”
Section: First Biological Mechanism Suggests That the Cellular Organelles And Membranes Are Controlled Through Their Lipidic Compositionmentioning
confidence: 99%
“… 165 Polyunsaturated fatty acids (PUFAs) and their analogs N‐arachidonoyl taurine have been found to speed up Kv7.1 channel opening and restore channel gating of many different mutant channels 226 PUFAs and their analogs are effective in shortening the cardiac action potential in pharmacologically prolonged ventricular action potential and QT interval in isolated guinea pig hearts 227 and in hIPSC‐CM. 228 Therefore, activators of Kv7.1 are also worth developing to treat LQT1 based on structure‐function studies on diverse IKs channel mutations. However, PUFAs analogs vary in selectivity and different effects for Kv7.1, Nav1.5, and Cav1.2 through nonidentical mechanisms.…”
Section: Conclusion and Perspectivementioning
confidence: 99%